SIN IS A PERSON: SOME ONTOLOGICAL METAPHORS IN THE BIBLE - C. Owiredu (Acta Theologica)
This article discusses the ontological metaphors relating to the personification of sin in the Bible. It aims to explore the metaphorical conceptualisation of sin as a person, as suggested in the sin expressions. Lakoff and Johnson’s (1980) Conceptual Metaphor Theory is used in analysing the data. The findings of the study indicate that sin is conceptualised as king, master, lord, paymaster, mother, and child. The use of these conceptual metaphors indicates that the writers of the selected biblical texts intended to project a deeper meaning of sin beyond the literal meaning of sin in daily language. The ontological metaphorical use of sin in the Bible seems to give a greater effect in comprehension to the reader of the texts.